Clients Management in difficult situations - Urbina Rosas, Claudia (2015)
The relationship with our users is one of the fundamental processes that contribute to the success and strengthening of business; in daily interaction, it is normal to find some situations that get out of control, scenarios that can produce strong controversy and anger in customers. Proper and timely management of these conditions can radically mark our relationships with customers and therefore the development of enterprises.